PENGARUH LUMPUR PT LAPINDO BRANTAS TERHADAP KOROSI PADA STRUKTUR BAJA - Herman Pratikno (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2008)
The natural gas mine owned by PT Lapindo Brantas failed to be operated. This has caused the hot mud to blow out from the exploration well in Porong, Sidoarjo, East Java. The mud contains corrosive substances, which can cause corrosion to the steel structure. This research was aimed to determine the corrosion rate and types of corrosion, which could be caused by the mud. The results were compared to those caused by the rice field mud. Railway steel ASTM A-607, water pipe JIS G3106, lighting pole ASTM A572 Gr 65, oil and gas pipe ASTM A53 steel materials were tested during this research. The corrosion tests were done according to ASTM G 48 at normal temperature for 72 hours. The results showed that the corrosion rate was about 4.53 times faster than the corrosion rate which was caused by the rice field mud. The most resistant steel structure was the gas pipe.